Investigating Employee Satisfaction and Corporate Performance: Mining From Employer Branding: Menyelidiki Kepuasan Karyawan dan Kinerja Perusahaan: Menambang dari Pencitraan Merek Perusahaan - Izharuddin, Muhammad; Susilo Hadi, Faizal (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the relationship between employee satisfaction and corporate performance using data mining techniques on anonymous employee feedback. The study tries to determine how employee satisfaction affects company performance. Textual analysis of employee reviews was carried out using a data mining approach in order to find relationships between satisfaction and performance. The investigation highlighted major employee satisfaction elements such as salary and benefits, work-life balance, workload, career development, and management, all of which have a significant impact on business success. Interestingly, work-life balance and workload were found to be negatively correlated with performance. These findings offer useful insights for employer branding efforts, underlining the need of addressing certain components of employee happiness in order to improve overall corporate performance.